The History of Bail and Pretrial Release (2010) - Timothy R. Schnacke, Michael R. Jones, Claire M. B. Brooker (My University, 2016)
This report reviews the history of bail and pretrial release, focusing on the roots of the bail system in medieval England and its progression in time in the United States. The report addresses the rise of the commercial money bail bondsman, relevant U.S. case law, the Manhattan Bail Project and the emergence of pretrial services programs in the U.S., and bail reform movements in the past few decades.